Myofilament Function in Health and Disease - Julien Ochala (Frontiers Research Topics, 2017)
The present E-book, consisting of a compilation of original articles and reviews, presents how myofilaments are regulated in cardiac and skeletal muscles and trigger contraction. Additionally, this E-book gives insights into their dysregulation in a number of muscle disorders.